Building Network Implementation Capacity: Evidence from China. Issue 2 (2nd April 2016) - Wang, XiaoHu; Chen, Kai; Berman, Evan M.
ABSTRACT: Network research increasingly draws attention to capacity affecting outcomes. This study examines network implementation capacity and develops a framework that focuses on three dimensions: financial, managerial, and technical capacity. It also contributes by focusing on the Network Administrator Organization (NAO)-type network. Based on a case study of two large eco-financing networks in China, this study finds positive impacts of network implementation capacity on policy outcomes. It also draws attention to network strategies and their impact on capacity. It identifies the positive effect of efforts to maintain network stability as well as negotiation and participation strategies on network implementation capacity. This study draws attention to implementation capacity as a determinant of network outcomes and suggests that studies in public administration give greater attention to NAO-type networks.